2009
DOI: 10.1007/s00018-009-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding the structure and function of general transcription factor TFIID

Abstract: The general transcription factor TFIID is a macromolecular complex comprising the TATA-binding protein (TBP) and a set of 13-14 TBP associated factors (TAFs). This review discusses biochemical, genetic and electron microscopic data acquired over the past years that provide a model for the composition, organisation and assembly of TFIID. We also revisit ideas on how TFIID is recruited to the promoters of active and possibly repressed genes. Recent observations show that recognition of acetylated and methylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 89 publications
2
70
0
3
Order By: Relevance
“…Previous studies have shown that nine of the 14 TFIID TAFs contain a sequence motif homologous to histones, called the histone fold domain (HFD), which mediates protein–protein interactions (reviewed in Cler et al, 2009; Papai et al, 2011). These nine TAFs can form five specific heterodimers: TAF3–10, TAF6–9, TAF4–12, TAF8–10 and TAF11–13.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that nine of the 14 TFIID TAFs contain a sequence motif homologous to histones, called the histone fold domain (HFD), which mediates protein–protein interactions (reviewed in Cler et al, 2009; Papai et al, 2011). These nine TAFs can form five specific heterodimers: TAF3–10, TAF6–9, TAF4–12, TAF8–10 and TAF11–13.…”
Section: Discussionmentioning
confidence: 99%
“…The TATA box-binding protein (TBP) subunit of TFIID recognizes the TATA box element and can substitute for TFIID in transcription in vitro. Additional TBP-associated factor (TAF) subunits of TFIID recognize the initiator (Inr) and other core promoter elements and contribute to functional interactions between the general transcription machinery and DNA-binding transcription factors and coregulators (1,8,9). TBP has also been shown to be an essential component of SL1 and TFIIIB, which are multisubunit general transcription factors for RNA polymerases I and III, respectively (10 -16).…”
mentioning
confidence: 99%
“…Promoter-specific transcription by RNA polymerase II depends on the general initiation factors TFIIA, 2 -B, -D, -E, -F, and -H, which are the minimal set of factors needed for assembly of the preinitiation complex and subsequent initiation of transcription (1)(2)(3)(4). The activity of RNA polymerase II and the general transcription factors is controlled by a host of DNAbinding transcription factors, the Mediator of RNA polymerase II transcription, and other coactivators and corepressors (5)(6)(7).…”
mentioning
confidence: 99%
“…Le facteur de transcription TFIID est l'un de ces coactivateurs et contient TBP ainsi que 14 sous-unités nommées TAF pour TBP associated proteins [3]. La structure atomique de TBP montre que cette protéine adopte une forme de croissant et interagit avec la boîte TATA par l'intermédiaire de sa face concave [4].…”
Section: Le Coactivateur Tfiidunclassified
“…La structure atomique de TBP montre que cette protéine adopte une forme de croissant et interagit avec la boîte TATA par l'intermédiaire de sa face concave [4]. Mais d'autres TAF, tel que TAF2, participent à la reconnaissance du promoteur et, dans certains cas, rendent facultative la présence d'une boîte TATA [3]. Plusieurs TAF, dont TAF4 et TAF12, établissent des liaisons avec des activateurs transcriptionnels et contribuent au recrutement de TFIID à proximité des gènes à transcrire.…”
Section: Le Coactivateur Tfiidunclassified